Application of the Academic Research Consortium High Bleeding Risk Criteria in an All-Comers Registry of Percutaneous Coronary Intervention - Natsuaki, Masahiro; Morimoto, Takeshi; Shiomi, Hiroki; Yamaji, Kyohei; Watanabe, Hirotoshi; Shizuta, Satoshi; Kato, Takao; Ando, Kenji; Nakagawa, Yoshihisa; Furukawa, Yutaka; Tada, Tomohisa; Nagao, Kazuya; et al. (Circulation. Cardiovascular interventions, 2019)
BACKGROUND:Recently, the Academic Research Consortium for High Bleeding Risk (ARC-HBR) has been proposed to standardize the definition of HBR, which was arbitrarily defined as a Bleeding Academic Research Consortium 3 or 5 bleeding ≥4% at 1-year. However, the prevalence and the expected bleeding event rate of HBR patients defined by ARC-HBR criteria are currently unknown in the real-world percutaneous coronary intervention practice. METHODS:We applied the ARC-HBR criteria in the CREDO-Kyoto (Coronary Revascularization Demonstrating Outcome Study in Kyoto) registry cohort-2, a multicenter registry that enrolled 13 058 consecutive patients who underwent their first percutaneous coronary intervention. The primary bleeding end point was defined as the Global Utilization of Streptokinase and Tissue plasminogen activator for Occluded coronary arteries moderate/severe bleeding. There were 5570 patients (43%) in the HBR group and 7488 patients in the no-HBR group. RESULTS:Cumulative incidence of the primary bleeding end point was much higher in the HBR group than in the no-HBR group (10.4% versus 3.4% at 1-year, and 18.9% versus 6.6% at 5-year, P<0.0001). Presence of each ARC-HBR major or even minor criterion, in isolation, with the exception of liver cirrhosis and prior ischemic stroke, was also associated with major bleeding risk higher than 4% at 1-year. Cumulative 5-year incidence of the primary bleeding end point got incrementally higher as the number of the ARC-HBR major criteria increased (≥3 majors49.9%, 2 majors30.6%, 1 major18.5%, ≥2 minors14.7%, and no-HBR6.6%, P<0.0001). CONCLUSIONS:ARC-HBR criteria successfully identified those patients with very HBR after percutaneous coronary intervention, who represented 43% of patients in this all-comers registry.